2016
DOI: 10.1063/1.4953519
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and periodicity of Culex quinquefasciatus Say, 1823 (Diptera: Culicidae) as early indicator of filariasis transmission in Pekalongan, Central Java, Indonesia

Abstract: Abstract. Culex quinquefasciatus Say, 1823 is an insect that served as a vector for urban lymphatic filariasis. The abundance of this mosquito could serve as an early indicator for filariasis transmission in endemic area. On the other hand, its active period could be key point for this disease elimination. The information of its activities and periodicity in Indonesia was still inadequate. This study was conducted to determine the periodicity of Cx. quinquefasciatus and its potency for the filariasis transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…As earlier study, the Culex mosquito has an abundance and different temporal pattern for their biting and resting activities (Astuti et al, 2016;Moise, 2018). This activities pattern maight be in uenced by the environmental changing as the temperature, humidity, and wind velocity.…”
Section: Genetic Variation and Dendogram Treementioning
confidence: 82%
“…As earlier study, the Culex mosquito has an abundance and different temporal pattern for their biting and resting activities (Astuti et al, 2016;Moise, 2018). This activities pattern maight be in uenced by the environmental changing as the temperature, humidity, and wind velocity.…”
Section: Genetic Variation and Dendogram Treementioning
confidence: 82%
“…quiquefasciatus is in line with the results of previous studies. 19,20 Therefore, it can be concluded that the W. bancrofti DNAs were found in Cx. quinquefasciatus and Ae.…”
Section: Discussionmentioning
confidence: 97%
“…This mosquito was mostly active in outdoor biting and the period of active was at 01 and 4 am 18 , while in Pasir Sari Village Pekalongan Selatan District the peak of active biting period was at midnight and around 02 pm. 15 This peak timing of the mosquito periodicity may synchronous with the abundant of mf in the peripheral blood.…”
Section: Dominancy and Periodicitymentioning
confidence: 89%
“…In the both areas the total number of 323 adult female mosquitoes had been collected and consisted of 8 species of the genus Culex and 1 species of Aedes aegypti. 15 However, in Jenggot Village (Pekalongan City) it is showed moderate diversity and more various the mosquitoes genus, which were 5 of mosquito genera, which were genera of Culex, Aedes, Armigeres, Anopheles, and the genus of Lutzia. This finding is different from the results of the research conducted by Arimurti (2008) which concluded that the Cx.…”
Section: Diversitymentioning
confidence: 99%
See 1 more Smart Citation